2007
DOI: 10.1159/000104222
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis following Olanzapine Therapy: A Report of Three Cases

Abstract: Context: Atypical antipsychotic agents (clozapine, olanzapine) have been linked to metabolic effects and acute pancreatitis. Case Report: We reviewed the inpatient and outpatient records of three patients who developed acute pancreatitis while being treated with olanzapine. The mean age of the patients was 37.7 years (range 18–54 years, 2 female, 1 male). No alternative cause of acute pancreatitis was found in two of the three patients. In the remaining patient, olanzapine may have contributed to acute pancrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…Olanzapine got approved by FDA in 1996 and it does not cause agranuloctyosis as a side effect. 7 Literature review regarding the interaction of olanzapine with lithium revealed a reported case of delirium and EPS in 2005. 8 Although literature review regarding interactions of olanzapine with clonazepam and zolpidem showed no significant data on PubMed.…”
Section: Discussionmentioning
confidence: 99%
“…Olanzapine got approved by FDA in 1996 and it does not cause agranuloctyosis as a side effect. 7 Literature review regarding the interaction of olanzapine with lithium revealed a reported case of delirium and EPS in 2005. 8 Although literature review regarding interactions of olanzapine with clonazepam and zolpidem showed no significant data on PubMed.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have also shown the ability of atypical antipsychotics to directly impair insulin signaling and fatty acid uptake and release in cultured adipocytes [208]. The most consistent clinical effect noted is a slight increase in serum triglycerides and reduction in HDL cholesterol leading to increased ratio of LDL to HDL cholesterol, but severe hypertriglyceridemia and pancreatitis can also occur [209][210][211].…”
Section: Atypical Antipsychoticsmentioning
confidence: 99%
“…More rarely, cases can apply with diabetic ketoacidosis, hyperglycemia and hyperlipidemia [5][6][7][8]11]. …”
Section: Hospitalization Daysmentioning
confidence: 99%